Priorities and Policies for Biotechnology in Argentina - Dellacha, Juan M. (International Service for National Agricultural Research, 2001)
The objective of this paper is to present the results from a workshop conducted in Argentina on biotechnology priority-setting in the agriculture and food sectors. The workshop was organized by the "Argentina Focal Point" of the Canadian Latin American Initiative in Biotechnology for Sustainable Development (CamBioTec) with the collaboration of and support from the Focal Point's host-institution, the foundation "Foro Argentino de Biotecnología".